Divine and Human Spirit in Rom 8:16. Paul and Epictetus on Free Will - Kowalski, Marcin (The Biblical Annals, 2022)
The article focuses on the phenomenon of free will in Paul, taking as the starting point Rom. 8:16. At the beginning, a concise exegetical analysis of Rom 8:16 is presented, placed in the rhetorical context of Rom 8. Subsequently, a comparison is drawn between Paul’s and Epictetus’s views on divine and human agency. First, the Epictetus’s idea of freedom is presented with a special emphasis on the notion of proairesis, understood as the true self of a person, responsible for free moral choices and actions. Next, the similarities and differences between the Epictetus’s and Pauline vision of free will are discussed. What connects the apostle and the philosopher are convictions that free will can exist in a divinely determined world and that human volition requires continuous education and subordination to God’s will. The elements that clearly distinguish Paul from Epictetus are the natural image of deity to be imitated in the human pursuit of freedom, and a genuinely relational, corporeal and emotive character of free will in the apostle. The psycho-somatic nature of human personality and will in Paul invites a dialogue between the apostle and modern science but it has to be carried out cautiously, bearing in mind the different methodologies, the idea of transcendent deity and Christological foundation upon which the Pauline idea of freedom and free will is built.